Applications of mesenchymal stem cells in skin regeneration and rejuvenation - Jo, Hantae; Brito, Sofia; Kwak, Byeong Mun; Park, Sangkyu; Lee, Mi Gi; Bin, Bum Ho (International Journal of Molecular Sciences, 2021)
Mesenchymal stem cells (MSCs) are multipotent stem cells derived from adult stem cells. Primary MSCs can be obtained from diverse sources, including bone marrow, adipose tissue, and umbilical cord blood. Recently, MSCs have been recognized as therapeutic agents for skin regeneration and rejuvenation. The skin can be damaged by wounds, caused by cutting or breaking of the tissue, and burns. Moreover, skin aging is a process that occurs naturally but can be worsened by environmental pollution, exposure to ultraviolet radiation, alcohol consumption, tobacco use, and undernourishment. MSCs have healing capacities that can be applied in damaged and aged skin. In skin regeneration, MSCs increase cell proliferation and neovascularization, and decrease inflammation in skin injury lesions. In skin rejuvenation, MSCs lead to production of collagen and elastic fibers, inhibition of metalloproteinase activation, and promote protection from ultraviolet radiationinduced senescence. In this review, we focus on how MSCs and MSC-derived molecules improve diseased and aged skin. Additionally, we emphasize that induced pluripotent stem cell (iPSC)-derived MSCs are potentially advanced MSCs, which are suitable for cell therapy.
Keywords: Animals; Humans; Mesenchymal Stem Cells; Regeneration; Rejuvenation; Skin; Skin Diseases; Wound Healing; Antiaging; Induced pluripotent stem cell; Mesenchymal stem cells; Skin regeneration; Skin rejuvenation; Wound healing